Liberia : Enhanced Initiative for Heavily Indebted Poor Countries; Decision Point Document, Debt Sustainability Analysis, and Staff Supplement. (IMF Staff Country Reports; Country Report ;, 2008)
This paper presents an assessment of Liberia's eligibility and qualification for assistance under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. The macroeconomic framework underlying the Debt Relief Analysis (DRA) in this paper was updated to reflect discussions on the policy framework underlying a proposed three-year Poverty Reduction and Growth Facility/Extended Fund Facility (PRGF/EFF)-supported program. Finally, this study discusses the floating completion point triggers. Fiscal policy has been anchored on a balanced cash-based budget. The government has also implemented other measures to address long-standing problems in financial management and economic governance.